Development of iSpring e-LKPD Based on Guided Discovery Learning on Hydrolysis of Salt Material for Class XI SMA/MA - Cahyani, Septi Windri (Edukimia, 2024)
The development of Science and Technology is very rapid, especially in education. Permendikbud No. 103 of 2014 states that learning is student centered and skilled in using technology with the teacher as a facilitator. The use of technology can expand learning activities by using e-LKPD, so that students can learn independently. This research develops interactive e-LKPD that utilize technology on hydrolysis of salt material. Hydrolysis of salt is a decomposition reaction that occurs between salt cations and anions with water in a solution. The purpose was to analyze the level of validity and practicality of iSpring e-LKPD based on guided discovery learning on salt hydrolysis material for class XI. The type of research used is Educational Design Research (EDR) with the Plomp development model. The research subjects were UNP chemistry lecturers, teachers and students at SMAN 14 Padang. Validity was reviewed from content validity, construct and media experts conducted by chemistry lecturers and teachers, while practicality through small group tests by students and teachers. Based on the results of the research analyzed using the Aiken's V formula of 0.83 declared valid, while in the teacher and student practicality test of 87% and 85% with a very practical category.